Management Impressions in The Role of Doctors and Nurses in The Mental Hospital Environment of Aceh Province - Maula Salsabila (Indo Publishing, 2026)
Impression management, in the concept of role, is the management of the impression displayed by a person according to the role they play. This impression management also leads to the assessment of the people they want to portray. This study aims to determine how doctors and nurses manage their impression management in dealing with their front region and back region in the workplace, as well as what obstacles doctors and nurses experience in managing their impression management towards mental patients. This study used descriptive qualitative research, where the informants were obtained through a purposive sampling method. To analyze this study, the researcher used Erving Goffman's Dramaturgy theory. Data were collected through interviews, in-depth observations, and literature studies, and then analyzed using a qualitative approach. The results of this study showed a positive impression between health workers towards patients and their families, this also indicates that the services available at the Aceh Provincial Mental Hospital are improving. Doctors and nurses are also able to carry out their front region consistently within the scope of their work. However, the impression displayed among fellow workers does not always go well, namely the obstacles experienced by doctors and nurses when interacting and dealing with mental patients with various forms of medical backgrounds. Then there's the impact of work fatigue and differing understandings. The appearances in the front region are also inextricably linked to the influence of the back region, where doctors and nurses prepare themselves as best as possible to be judged well on their work. Therefore, when healthcare workers project their impressions to those around them, dramaturgy theory can be seen in the way doctors and nurses act and carry themselves in their roles.